Phase equilibrium and partition coefficient of selected pesticides and nitrophenols in double and triple-phase liquid-phase microextraction - Zainal Abidin, Nurul Auni (2009)
A two-phase and three-phase hollow fiber-protected liquid-phase microextraction method (HF-LPME) has been developed and used for the determination of partition coefficient and analysis of selected pesticides and nitrophenols in water samples. For two-phase HF-LPME, the analysis was performed by gas chromatography-electron capture detector (GC-ECD). Extraction conditions of the selected pesticides were optimized. The following conditions have been selected as the optimum extraction conditions: toluene as organic solvent, 4 mL water samples, 20 min extraction time, 850 rpm stirring rate, 1.8 cm HF length, 1.5% (w/v) NaCl content, and pH 3. The analytes were extracted from 4 mL donor phase through 4 µL of an organic solvent immobilized in the pores of a porous polypropylene hollow fiber and then into the acceptor phase present inside the hollow fiber. Correlation coefficients (r2) of 0.996-0.997 and limits of detection (LOD) of 0.0026-0.0028 µg/L were achieved under the optimized conditions. The proposed method provided good average enrichment factors of up to 350-fold and successfully determined the partition coefficient for the selected analytes that were found to be directly correlated to the enrichment factor. In the three-phase HF-LPME technique coupled with HPLC, nitrophenols were extracted from 2.5 mL aqueous solution with the adjustment of pH in the range of 3.0-5.0 (donor solution) into an organic phase (1-hexanol) immobilized in the pores of the hollow fiber and finally back-extracted into 5.0 µL of the acceptor microdrop (pH 12.0) located at the end of the microsyringe needle. After a prescribed back-extraction time, the acceptor microdrop was withdrawn into the microsyringe and directly injected into the HPLC system under the optimum conditions (donor solution: 1.0 M H3PO4, pH 3.0-5.0; organic solvent: 1-hexanol; acceptor solution: 5 µL of 0.1 M NaOH, pH 8.0-12.0; agitation rate: 1050 rpm; extraction time: 15 min). The calibration curve for these analytes was linear in the range of 0.6-200 µg/L with r2 > 0.9994 was achieved under the optimized conditions. The enrichment factors of up to 500-fold were obtained. In this work, determination of analytes partition coefficients in three-phase HF-LPME has been successfully achieved. This study found that the partition coefficient (Ka/d) values were high for 2-nitrophenol and 3-nitrophenol and the individual partition coefficients (Korg/d and Ka/org) promoted efficient simultaneous extraction from the donor through the organic phase and further into the acceptor phase. Both methods were successfully applied for the analysis of water samples.